Evaluasi Sistem Manajemen Persediaan untuk Mencegah Stockout Dan Mencapai Kepuasan Pelanggan (Studi Kasus Industri Distribusi Listrik) - Pratiwi, Kuniarti; Nurjanah, Siti (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
Inventory management plays a vital role in ensuring product availability and customer satisfaction, particularly in the electrical distribution industry, where demand tends to be dynamic. This study aims to evaluate the effectiveness of inventory management systems at PT XYZ, which has implemented an ERP system integrated with e-Kanban, yet still faces challenges in fulfilling customer demand on time. A key issue identified is the high rate of delivery delays, reaching 61%, primarily caused by manual buffer stock management and inconsistent forecasting accuracy. The analysis methods employed include the calculation of Economic Order Quantity (EOQ), Safety Stock (SS), Reorder Point (ROP), and Mean Absolute Percentage Error (MAPE) to measure forecasting accuracy. The results show that EOQ ranges from 102 to 207 units per order, with significant potential for reducing ordering costs. However, 62.5% of products have actual Safety Stock below optimal levels, increasing the risk of stockouts. The current ROP has not effectively triggered timely reorder due to a lack of consideration for weekly demand fluctuations. The average MAPE value of 14.19% indicates sufficient forecast accuracy, though several products exceed 30%, reflecting notable discrepancies between forecasted and actual demand. In conclusion, the current inventory system at PT XYZ requires improvement, especially in the adjustment of SS and ROP based on real-time data and the automation of buffer stock management. These measures are expected to reduce the risk of stockouts, improve inventory cost efficiency, and maintain customer satisfaction.